2017
DOI: 10.4995/eurocall.2017.7145
|View full text |Cite
|
Sign up to set email alerts
|

Profiling language learners in hybrid learning contexts: Learners’ perceptions

Abstract: This article discusses formal and informal foreign language learning before university level. The focus is on beginning university students' perceptions of their earlier learning experiences, especially in digital contexts. Language learners' digital competence is a part of their everyday lives, but its relationship to learning in and outside educational settings is still relatively seldom studied. The article discusses learning in formal and informal (i.e., hybrid) contexts and digital learning profiles −that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, not all young learners who were born in the digital age could be categorized as digital native due to their skills which might not match to the concept of implications. For an example, they may not transfer their knowledge and skills of social media to support language learning (Lintunen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all young learners who were born in the digital age could be categorized as digital native due to their skills which might not match to the concept of implications. For an example, they may not transfer their knowledge and skills of social media to support language learning (Lintunen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, however, there have been a number of studies presenting favourable attitudes towards mobile learning (Briz-Ponce, Pereira, Carvalho, Juanes-Méndez, & García-Penalvo, 2017;Busulwa & Bbuye, 2018;Iqbal, Khan, & Malik, 2017;Lintunen, Mutta, & Pelttari, 2017;Thi Thanh Thuy Nguyen & Yukawa, 2019;Quan, 2019;Steel, 2017). A 2019 literature review on MALL in higher education contexts revealed that while mobile learning "seems to have secured its place in teaching and learning foreign languages" (Metruk, 2019, p. 5), attitudes still played an important role in its adoption.…”
Section: Diverse Attitudes Towards Mobile Learningmentioning
confidence: 99%
“…While most studies on learner profiling, both person-oriented and technology-based, took a quantitative approach (Csizer & Dornyei, 2005), there were a few studies that collected data qualitatively (Fearon et al, 2017;Takahashi, 2015) and those employed an empirical mixedmethods approach (S. B. Dias & Diniz, 2014;Lintunen et al, 2017;Tsuda & Nakata, 2013).…”
Section: Learner Profilingmentioning
confidence: 99%
See 2 more Smart Citations